2015
DOI: 10.1007/s00268-015-3343-7
|View full text |Cite
|
Sign up to set email alerts
|

Liver Exposure Using Sterile Glove Pouch During Laparoscopic Right Liver Surgery in Hepatocellular Carcinoma Patients

Abstract: Our data suggests that a sterile glove pouch could enhance exposure in surgical field, which results in decrease in blood loss and procedure time. More studies with large sample size, large tumor size, and longer follow-up are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…To solve the problem of handling the right liver in LLR - wherein the surgeon’s left hand is not able to reach behind the liver, as it is in OLR - the hand-assisted approach[19], robotic liver resection (RLR)[20], and the approach using spacers, such as the sterile glove pouch[21], have been proposed for LLR of posterior lesions.…”
Section: Llr Approaches For Tumors Located In the Posterosuperior Livermentioning
confidence: 99%
See 1 more Smart Citation
“…To solve the problem of handling the right liver in LLR - wherein the surgeon’s left hand is not able to reach behind the liver, as it is in OLR - the hand-assisted approach[19], robotic liver resection (RLR)[20], and the approach using spacers, such as the sterile glove pouch[21], have been proposed for LLR of posterior lesions.…”
Section: Llr Approaches For Tumors Located In the Posterosuperior Livermentioning
confidence: 99%
“…Bin et al[21] reported that the liver exposure achieved by means of the sterile glove pouch applied as a spacer led to shortened operative time, decreased bleeding and reduced levels of post-operative alanine aminotransferase/aspartate aminotransferase in right liver surgery, including S7 segmentectomy. The usage of spacers, such as the sterile glove pouch, may help in posterosuperior resections; specifically, their use, without disturbance of the operative view and to facilitate manipulation in the small subphrenic cage, should be established in LLR for posterosuperior lesions in S7 segmentectomy and partial resections.…”
Section: Llr Approaches For Tumors Located In the Posterosuperior Livermentioning
confidence: 99%
“…Patients were placed in a supine position, with a surgeon on the right-hand side and a surgeon-assistant and camera-assistant on the left-hand side. The systematic ‘7+3’ approach was used in all LRPHs, based on procedures described previously ( 15 , 20 22 ), including low central venous pressure (CVP), intermittent clamping of the hepatic pedicle, pneumoperitoneum at 12 mmHg, parenchymal section with ultrasonic dissector and sterile glove pouch. The seven key points include the following: Special triangular positioning ( 15 , 23 27 ), lifting the right arm, rotating internally with an angle of 90° elbow flexion fixed on the support and elevating the right side of the body at an angle of 15–30° (β) inclined to left, which looks like a triangle ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The systematic ‘7+3’ approach was used in all LRPHs, based on procedures described previously ( 15 , 20 22 ), including low central venous pressure (CVP), intermittent clamping of the hepatic pedicle, pneumoperitoneum at 12 mmHg, parenchymal section with ultrasonic dissector and sterile glove pouch. The seven key points include the following: Special triangular positioning ( 15 , 23 27 ), lifting the right arm, rotating internally with an angle of 90° elbow flexion fixed on the support and elevating the right side of the body at an angle of 15–30° (β) inclined to left, which looks like a triangle ( Fig. 1 ); improved trocar location ( 9 ), the observation port used in the present study was located to the right of the umbilicus, the main operating port was located in the right collarbone midline and the right axillary front-line at the same level as the umbilicus, and the assistant ports were located below the process and at the midpoint between the xiphoid process and the umbilicus; the ‘grasping and pulling’ method ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation